The Bicycle Spy - McDonough, Yona Zeldis (New York : Scholastic Press, 2016)
Twelve-year-old Marcel loves riding his bicycle, and dreams of competing in the Tour de France, but it is 1942 and German soldiers are everywhere, stopping him as he delivers bread from his parents' bakery around Aucoin-- then one day he discovers that it is not just bread he is delivering, and suddenly he finds himself in position of dangerous secrets about his parents and his new friend from Paris, Delphine.
Includes bibliographical references.
Keywords: World War, 1939-1945 -- Juvenile fiction -- Underground movements -- France; Secrecy -- Juvenile fiction; Families -- Juvenile fiction -- France; Jews -- Juvenile fiction -- History -- 20th century -- France; Cycling -- Juvenile fiction; Adventure stories; War stories; World War, 1939-1945 -- Fiction -- Underground movements -- France; Secrets -- Fiction; Family life -- Fiction -- France; Jews -- Fiction -- France; Bicycles and bicycling -- Fiction; Adventure and adventurers -- Fiction; France -- Juvenile fiction -- History -- German occupation, 1940-1945; France -- Fiction -- History -- German occupation, 1940-1945; Action and adventure fiction